The Sports Industry in the Service Sector During the Covid 19 Pandemic in Bandar Lampung - Armanjaya, Satria; Rustiadi, Tri; Rumini, Rumini (Journal of Physical Education and Sports, 2021)
This research is motivated by the condition of the sports industry in Bandar Lampung during the pandemic. The sports service industry is experiencing the effects of the COVID-19 pandemic that began in early 2020. This is a qualitative study employing a phenomenological design. The investigation was conducted in Bandar Lampung on April 5, 2021. The research collected data from service and rental service actors, Technical Implementing Service Unit of Youth, and Sport Office, Lampung Regency, and the community as sports participants. Techniques for data collection include observation, interviews, and documentation. Data analysis is composed of 4 interacting components: data collection, data reduction, data display, and conclusion. The findings of this study show that the condition of Bandar Lampung’s sports service industry is currently being affected by the COVID-19 pandemic. Due to the obstacles encountered in the field, sports service actors are powerless to intervene. With the reopening of their businesses, sports service actors implemented strategies to ensure their businesses continued during the pandemic, including limiting operating hours, restricting visitors, and implementing health protocols. Certain perpetrators of sports services work additional jobs to supplement their income. Online media and offering discounts are two strategies for re-engaging people in sports. The research concludes that the sports service industry in Bandar Lampung was experienced a decrease in income during the COVID-19 pandemic. Actors in sports services can resume operations if they adhere to strict health protocols and continue to be monitored by the regional COVID-19 cluster.